Design, Modeling and Evaluation of Protective Relays for Power Systems - Kezunovic, Mladen; Ren, Jinfeng; Lotfifard, Saeed (Springer International Publishing : Imprint: Springer, 2016)
· Provides hands-on experience designing relays and evaluating performance · Explains in-depth the theory needed to understand how the relays operate · Offers practical insights on how relays can be used and how to optimize performance This book is a practical guide to digital protective relays in power systems. It explains the theory of how protective relays work in power systems, provides the engineering knowledge and tools to successfully design them, and offers expert advice on how they behave in practical circumstances. This book helps readers gain technical mastery of how the relays function, how they are designed, and how they perform. This text not only features in-depth coverage of the theory and principles behind protective relays, but also includes a manual supplemented with software that offers numerous hands-on examples in MATLAB. A great resource for protective relaying labs and self-learners, it provides lab experiments unavailable elsewhere. The book is suitable for advanced courses in Digital Relays and Power Systems Fault Analysis and Protection, and will prove to be a valuable resource for practitioners in the utility industry.